The mechanical, thermal and morphological properties of graphene nanoplatelets filled poly(lactic acid)/epoxidized palm oil blends / Buong Woei Chieng ... [et al.] - Buong, Woei Chieng; Ibrahim, Nor Azowa; Wan Yunus, Wan Md Zin; Hussein, Mohd Zobir (Research Management Institute (RMI), 2014)
Poly(lactic acid) (PLA)-based nanocomposites filled with graphene nanoplatelets (xGnP) that contains epoxidized palm oil (EPO) as plasticizer were prepared by melt blending method. PLA was first plasticized by EPO to improve its flexibility and thereby overcome its problem of brittleness. Then, xGnP was incoporated into plasticized PLA to enhance its mechanical properties. Plasticized and nanofilled PLA nanocomposites (PLA/EPO/xGnP) showed improvement in the elongation at break by 3322% and 61% compared to pristine PLA and PLA/EPO, respectively. The use of EPO and xGnP increases the mobility of the polymeric chains, thereby improving the flexibility and plastic deformation of PLA. The nanocomposites also resulted in an increase of up to 26.5% in the tensile strength compared with PLA/EPO blend. XRD pattern showed the presence of peak around 26.5° in PLA/EPO/xGnP nanocomposites which corresponds to characteristic peak of graphene nanoplatelets. Plasticized PLA reinforced with xGnP showed that increasing the xGnP content triggers a substantial increase in thermal stability. Crystallinity of the nanocomposites as well as cold crystallization and melting temperature did not show any significant changes upon addition of xGnP. However, there was a significant decrease of glass transition temperature up to 0.3wt% of xGnP incorporation. The TEM micrograph of PLA/EPO/xGnP shows that the xGnP was uniformly dispersed in the PLA matrix and no obvious aggregation was observed.